Case series: Heinz body formation in 13 multimorbid dogs following metamizole administration - Geisen, Vera; Hartmann, Katrin; Dörfelt, René (Frontiers in Veterinary Science, 2023)
Background: Heinz Body (HB) anemia is a result of oxidative damage and is an uncommon condition in dogs compared with cats. In this retrospective case series, clinical features, laboratory values, concurrent diseases, and outcome of 13 multimorbid dogs developing HBs after receiving metamizole are reported. Case description: Ten of the 13 dogs in this case series that developed HBs were older and multimorbid, but the only feature all dogs had in common was receiving metamizole. HBs were detected in seven out of 13 dogs within a few days (3 – 10 days) after starting metamizole treatment. The metamizole dose was 38 – 159 mg/kg/day. Highest percentage of HBs detected was 28 – 95% (mean, 46%). There was no correlation between the percentage of HBs and the daily dose of metamizole. All but one dog had mild-to-severe anemia at the time of the highest HB appearance. The number of HBs did not correlate with the hematocrit at that time. In 8/12 dogs, no stress leukogram was present. Approximately half of the dogs with HBs also had evidence of gastrointestinal hemorrhage, which could have masked additional oxidative damage. Conclusion: In multimorbid dogs that develop regenerative anemia after receiving metamizole, hemolysis due to HB development caused by oxidative damage should be considered as an important differential diagnosis.